Smart Solar Power System with Load Prioritization for Rural Areas and Islands - Lim, Kian Ann; Dirman Hanafi, (Evolution in Electrical and Electronic Engineering, 2025)
Solar energy is a free, renewable, and clean energy source that can be an alternative to diesel generators in rural electrification. But it is highly weather-dependent, making it unreliable, especially without a proper energy management system and uncontrolled load usage. This project proposes a smart solar power system with a load prioritization mechanism that aims to improve reliability by gradually shedding lower-priority loads as the battery’s State of Charge (SoC) decreases, preserving power for critical loads. Using a voltage divider circuit, the programmed Arduino UNO safely monitors the State of Charge (SoC) of the battery and smartly controls relays connected to the loads. The system's voltage measuring accuracy and relay response to load prioritization were tested before conducting an experiment to evaluate the efficiency and reliability improvements between the traditional and designed systems. The accuracy of the measured voltage values has been proven high, with each measurement having only a minimal deviation (